Does Co-Morbid Obsessive–Compulsive Disorder Modify the Abnormal Language Processing in Schizophrenia Patients? An fMRI Study - Bleich-Cohen, Maya; Poyurovsky, Michael; Hendler, Talma; Weizman, Ronit; Sharon, Haggai (Frontiers in Human Neuroscience, 2014)
Background: Impaired language processing is one of the most replicated findings in functional brain studies of schizophrenia. This is demonstrated by reduced activations and decreased language lateralization in left prefrontal language areas (i.e. BA44/45,- the inferior frontal gyrus, IFG). This finding was documented both in chronic as well as in first-episode schizophrenia patients, arguing for a neurobiological marker for schizophrenia. In a previous study we demonstrated the specificity of this finding to schizophrenia patients compared to OCD patients in which language processing was similar to healthy controls. Since a sizable proportion of schizophrenia patients have co-morbid obsessive-compulsive disorder (OCD), we further sought to elucidate whether OCD attenuates abnormal prefrontal language lateralization in this unique group of schizo-obsessive patients compared to their non-OCD schizophrenia counterparts. Methods: We used functional magnetic resonance imaging (fMRI) to investigate regional activation and language lateralization in the left and right IFG and inter-hemispheric functional connectivity (FC) during a language task in 14 schizophrenia patients with OCD, compared to 17 schizophrenia patients without OCD, 13 OCD patients and 14 healthy controls. Results: No between-group differences were found in the behavioral measurements of word generation. However, while OCD patients were indistinguishable from healthy volunteers, a similarly reduced lateralization in the IFG and diminished inter-hemispheric FC was noted in the two schizophrenia groups with and without OCD. Conclusions: The co-occurrence of OCD in schizophrenia does not attenuate abnormal processing of language as reflected by regional IFG activity and functional connectivity. These results further support the notion that these language processing abnormalities are characteristic of schizophrenia and that Schizophrenia-OCD combined psychopathology is more akin to schizophrenia than to OCD